Research on Deterioration Mechanism of Concrete Materials in an Actual Structure. (13th May 2014) - Zhang, Shiping; Dong, Xiang; Zhang, Houxian; Deng, Min
Abstract : The cause for deterioration of the concrete structure located in severe environment has been explored both in field and in laboratory. Serious cracking and spalling appeared upon surface of the concrete structure soon after the structure was put into service. Both alkali-aggregate reaction and freeze-thaw cycles may result in similar macro visible cracking and spalling. The possibility of alkali-aggregate reaction was excluded by both field survey and lab examination such as chemical analysis, petrographic analysis, and determination of alkali reactivity of aggregates. According to results of freeze-thaw cycles, impermeability testing, and microstructure analysis, it is deduced that the severe environmental conditions plus the relatively inferior frost resistance cause the deterioration of concrete. Usage of air entraining admixture can improve frost resistance and impermeability. Furthermore, new approaches to mitigate the deterioration of concrete used in severe environmental condition are discussed.